1994
DOI: 10.1210/endo.134.5.7512496
|View full text |Cite
|
Sign up to set email alerts
|

Coculture of primary rat hepatocytes and nonparenchymal cells permits expression of insulin-like growth factor binding protein-3 in vitro.

Abstract: In biological fluids, the insulin-like growth factors (IGFs) are associated with binding proteins (IGFBPs), which modify IGF distribution and action. Circulating IGFs are bound predominantly to IGFBP-3, of apparent hepatic origin, but regulation of IGFBP-3 has been difficult to dissect because of the lack of systems suitable for examining hepatic production of IGFBP-3 in vitro. In the present studies, IGFBP-3 expression was identified primarily in hepatic nonparenchymal cells, particularly Kupffer and sinusoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 6 publications
6
37
0
1
Order By: Relevance
“…Plasma IGFBP-3 levels are primarily influenced by GH and nutritional status: GH stimulates hepatic synthesis of IGFBP-3, probably indirectly through IGF-I (Villafuerte et al 1994), and fasting or malnutrition causes a decrease in circulating IGFBP-3 (Clemmons & Underwood 1991). In fish, candidates for IGFBP-3 have been detected based on molecular size and responses to GH injection and fasting on Western ligand blotting (Kelley et al 1992, Siharath et al 1995, Shimizu et al 1999, Park et al 2000.…”
Section: Figurementioning
confidence: 99%
“…Plasma IGFBP-3 levels are primarily influenced by GH and nutritional status: GH stimulates hepatic synthesis of IGFBP-3, probably indirectly through IGF-I (Villafuerte et al 1994), and fasting or malnutrition causes a decrease in circulating IGFBP-3 (Clemmons & Underwood 1991). In fish, candidates for IGFBP-3 have been detected based on molecular size and responses to GH injection and fasting on Western ligand blotting (Kelley et al 1992, Siharath et al 1995, Shimizu et al 1999, Park et al 2000.…”
Section: Figurementioning
confidence: 99%
“…All three components of the 150 kDa complex are produced by distinct hepatic cell types and, specifically, hepatocytes synthesize the IGF peptide and the acidlabile subunit (ALS), while Kupffer and sinusoidal endothelial cells produce IGFBP-3 (10)(11)(12). Regarding the regulation of the synthesis of the 150 kDa complex subunits, it has been established that, besides GH and nutrients (13), several other factors, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…epidermal growth factor (EGF) (14), fibroblast growth factor and platelet-derived growth factor can modulate IGF-I production in liver (14) and in other target cells (15), where the IGF peptide can act through autocrine and paracrine mechanisms. In addition, the synthesis of IGFBP-3, the binding subunit of the complex, can be regulated by several factors in liver (12) and in other cell types (16). Clinical data obtained in hypopituitary subjects (17) or in subjects treated with GH, alone or in combination with IGF-I (18,19), demonstrate that ALS is primarily under the control of GH.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that these proteins are produced in different hepatic cell populations. Rat hepatocytes have been shown to secrete IGFBP-1, IGFBP-2, and IGFBP-4 (Bö ni-Schnetzler et al, 1990;Menuelle et al, 1995;Villafuerte et al, 1991), whereas IGFBP-3 expression was only found in Kupffer cells, endothelial cells, and hepatic stellate cells (Scharf et al, 1995(Scharf et al, , 1996(Scharf et al, , 1998aVillafuerte et al, 1994Villafuerte et al, , 1995. IGF-I is mainly released from hepatocytes (Kachra et al, 1991;Scharf et al, 1998a;Scott et al, 1985aScott et al, , 1985b.…”
mentioning
confidence: 99%